2018
DOI: 10.17221/38/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

First report of ticks in the subcutaneous tissue of the raccoon dog Nyctereutes procyonoides

Abstract: Ticks are common ectoparasites of animals; they also carry many tick-borne pathogens that are often detrimental for the health of both animals and humans. These parasites have been found in subcutaneous tissue, mainly in red foxes (Vulpes vulpes), but the reason for this is unknown. In this study we report the first occurrence of the tick in an unusual location in the subcutaneous tissue of the raccoon dog Nyctereutes procyonoides. The study was carried out on two adult male raccoon dogs, hunted in Western Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…So far, the subcutaneous presence of ticks was mostly reported from red foxes [13][14][15][16][17][18][19][20][21] Only single case reports of subcutaneous ticks in raccoon dogs and from one single domestic dog exists at the moment [22,23] In a study inspecting 134 roe deer furs from inside and outside, only external ticks were found and none in the subcutaneous tissue [37]. Thus far, little is currently known about this phenomenon, leaving questions concerning the mechanisms as to how ticks become subcutaneous and which animals can be affected.…”
Section: Body Partmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the subcutaneous presence of ticks was mostly reported from red foxes [13][14][15][16][17][18][19][20][21] Only single case reports of subcutaneous ticks in raccoon dogs and from one single domestic dog exists at the moment [22,23] In a study inspecting 134 roe deer furs from inside and outside, only external ticks were found and none in the subcutaneous tissue [37]. Thus far, little is currently known about this phenomenon, leaving questions concerning the mechanisms as to how ticks become subcutaneous and which animals can be affected.…”
Section: Body Partmentioning
confidence: 99%
“…Besides red foxes, single case reports of subcutaneous ticks were previously recorded in raccoon dogs (Nyctereutes procyonoides) from Poland [22], in a dog from Sweden [23] and in a child from South Korea [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ixodes ricinus is the most prevalent tick species in Europe that parasitizes mainly on mammals and has a very wide host range ( Randolph, 2009 ; Medlock et al, 2013 ; Rizzoli et al, 2014 ). Matysiak et al (2018) previously observed this tick species in the subcutaneous tissue of raccoon dogs in Poland. Dermacentor reticulatus can also infest a wide range of hosts, which includes humans and it shows high tolerance to a changing environment ( Földvári et al, 2016 ; Matysiak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 75%
“…Despite the sample size of wolves in our study being still relatively limited, though the highest in literature so far, the fact that no wolves presented SCT, and that among other canids, only five additional reports of SCT ticks were made in three raccoon dogs in Poland [ 12 ], a domestic dog in Sweden [ 13 ] and a golden jackal in Romania [ 10 ], support the hypothesis that the immune reaction of these canids in the early phases of tick insertion may be less intense than that activated by foxes, thus preventing the embedment process underneath the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In these surveys, prevalence of subcutaneous ticks (SCT hereafter) ranged between 15.4 and 88.1%, suggesting common occurrence of this previously neglected phenomenon [ 8 , 9 , 11 ]. Three additional SCT cases were reported in raccoon dogs ( Nyctereutes procyonoides ) in Poland [ 12 ] and single cases in the golden jackal ( Canis aureus ) [ 10 ] and domestic dog ( Canis familiaris ) in Romania and Sweden, respectively [ 8 , 13 ]. No SCT were found in the grey wolf ( Canis lupus ) and other, non-canid, hosts, including members of the Felidae and Mustelidae families in Romania [ 10 ], but the sample size was quite limited in the case of the wolf and the Eurasian lynx ( Lynx lynx ).…”
Section: Introductionmentioning
confidence: 99%